2020
DOI: 10.1039/c9gc02484k
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy for CO2 utilization with waste plastics: conversion of hydrogen carbonate into formate using polyvinyl chloride in water

Abstract: A new and green approach for hydrogen carbonate reduction and PVC dechlorination in water in a single step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…[108] Jin and co-workers proposed the simultaneous PVC dechlorination and the CO 2 reduction [109,110] into valuable formate under hydrothermal conditions. [111] In the work, bicarbonate and carbonate salts were employed as the starting materials to represent absorbed CO 2 solutions. The PVC was added into the aqueous solutions and the mixtures were heated to about 300°C.…”
Section: Energy-associated Techniques For Plastic Treatmentmentioning
confidence: 99%
“…[108] Jin and co-workers proposed the simultaneous PVC dechlorination and the CO 2 reduction [109,110] into valuable formate under hydrothermal conditions. [111] In the work, bicarbonate and carbonate salts were employed as the starting materials to represent absorbed CO 2 solutions. The PVC was added into the aqueous solutions and the mixtures were heated to about 300°C.…”
Section: Energy-associated Techniques For Plastic Treatmentmentioning
confidence: 99%
“…Other than CO 2 capture, a recent study demonstrated the non-intuitive possibility of using PVC for CO 2 reduction, while achieving simultaneous de-chlorination of PVC. 55 Using aqueous HCO 3 − to simulate the CO 2 source when captured in alkaline solution, PVC was able to reduce hydrogen carbonate to formate at 300 °C in a batch tubular reactor. Mechanistic studies suggest that under alkaline conditions, PVC will undergo de-chlorination via elimination and substitution, forming a nucleophilic intermediate that could engage in redox reaction with hydrogen carbonate in water (Fig.…”
Section: Polymers For Co 2 Capture and Utilisationmentioning
confidence: 99%
“…1,2 To tackle with these problems, scientists have explored along different directions, such as the valorization of renewable feedstock alternatives to fossil fuels, [3][4][5][6] CO 2 capture and storage, 1 and CO 2 renery and utilization. [7][8][9][10] As a non-toxic, cheap, and abundant C1 renewable carbon resource, CO 2 utilization for value-added compounds and energy products furnishes as a promising approach to not only alleviating the greenhouse effect but also bringing about extra environmental and economic values. 11 So far, great achievements have been made in the chemical transformation of CO 2 into diverse chemicals, fuels, and materials.…”
Section: Introductionmentioning
confidence: 99%